2013
DOI: 10.2147/rmhp.s47723
|View full text |Cite
|
Sign up to set email alerts
|

The medication process in a psychiatric hospital: are errors a potential threat to patient safety?

Abstract: PurposeTo investigate the frequency, type, and potential severity of errors in several stages of the medication process in an inpatient psychiatric setting.MethodsA cross-sectional study using three methods for detecting errors: (1) direct observation; (2) unannounced control visits in the wards collecting dispensed drugs; and (3) chart reviews. All errors, except errors in discharge summaries, were assessed for potential consequences by two clinical pharmacologists.SettingThree psychiatric wards with adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Moreover, nurses have reported to be lacking in confidence when discussing treatment options with patients, carers and medical colleague (Bressington, Mui, & Wells, 2013). A lack of knowledge about these medicines can lead to errors during the management process as demonstrated by a relatively recent study that observed administration errors accounted for 75% of all medicine-related errors (Soerensen, Lisby, Nielsen, Poulsen, & Mainz, 2013) and can result in patient harm. For example, anecdotal evidence suggests that nurses frequently mistake the side effects of neuroleptic malignant syndrome or akathisia with psychotic agitation.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Moreover, nurses have reported to be lacking in confidence when discussing treatment options with patients, carers and medical colleague (Bressington, Mui, & Wells, 2013). A lack of knowledge about these medicines can lead to errors during the management process as demonstrated by a relatively recent study that observed administration errors accounted for 75% of all medicine-related errors (Soerensen, Lisby, Nielsen, Poulsen, & Mainz, 2013) and can result in patient harm. For example, anecdotal evidence suggests that nurses frequently mistake the side effects of neuroleptic malignant syndrome or akathisia with psychotic agitation.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“… 2 13–15 Published studies of PEs (and/or related ADEs) originate from the UK, 9 16–23 the USA 24–27 and Denmark. 28 In common with reviews of general hospital studies, 2 differences in study methods, settings and definitions preclude the synthesis of PE data from relevant studies to gain an overall measure of their impact. 13 15 29 …”
Section: Introductionmentioning
confidence: 99%
“…A number of PE studies carried out in mental health utilised incident/self-reports 21 23 with others using a retrospective medication chart review (with or without incident reports/case note review/direct observation). 16 17 24 25 28 Prospective identification of PEs in UK psychiatry has most commonly involved pharmacists checking prescription charts over different time periods, 9 18–20 22 yielding error rates of 2.2% 18 and 2.4% 22 of prescription items checked (two studies did not provide a denominator 19 20 ) and 31.3% of whole prescriptions checked. 9 Between 42.1% and 65% of PEs are administered to patients before correction by the pharmacist.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the rate of dispensing errors was more than 30%, higher than that reported in other studies. [ 36 , 37 ] Omission was the most frequent type of dispensing error. However and importantly, corresponding drugs were mainly analgesics and laxatives which were prescribed but administered only on patient demand.…”
Section: Discussionmentioning
confidence: 99%